Força e atividade elétrica dos músculos do quadril de indivíduos com osteoartrite de quadril - Melo, Cristiane de Sousa (Universidade Federal de São Carlos, 2020)
Introduction: Osteoarthritis (OA) is an inflammatory and degenerative joint's disease. The individuals affected by OA hip (OAH) can present a clinical alterations of gait, pelvic instability and the reduction of the quality of life. The following risk factors suggest the development of OAH how reduction in the strength of the periarticular muscles, can alterations changes in the muscular activation patterns. However, there is poor knowledge about the clinical picture in non-advanced degrees of hip's osteoarthritis. Objectives: This work aim's to analyze the strength and the electrical activity of hip's joint muscles, the functional impairment and their impacts on the quality of life of individuals affected by the OAQH considering the initial and moderate degrees of the disease in comparison with healthy individuals. Materials and methods: This work analyzed 62 individuals of both genders considering the age group from 40 to 74 years old. They will be divided into 2 groups as follows: the control group (n=30) composed by individuals without hip's osteoarthritis diagnosis (healthy individuals) and the hip's osteoarthritis group (n=32) composed by individuals diagnosed with the hip's osteoarthritis in levels II and III (based on the Kellgren's and Lawrence's criterions,1957). The individuals' assessmented is composed of the following analysis: anthropometric measurements, functional tests sit and stand, 40-meter walk up and down steps. Assessment strength concentric and eccentric isokinetic performance of the abductors and adductors, flexors and extensors, medial and lateral hip rotators, an used isokinetic dynamometer was used Biodex Multi Joint System III, at 30º/s. The analysis of the electrical activity of the rectus femoris, gluteus maximus and medius muscles was performed synchronized to the isokinetic evaluation. Results: The three functional tests were significantly different in relation to the CG (p <0.001). In the concentric isokinetic evaluation, a difference was found for the Abductor (p = 0.002), Adductor (p = 0.03) and Medial Rotation Torques (p = 0 , 03), with GOAQ lower values, for Eccentric Torques were Abduction (p = 0.0038), Flexion (p = 0.006) and Medial Rotation (p = 0.005), with GOAQ also demonstrated lower values. Conclusion: With the results of the present study, we can suggest that in the initial degrees of OAQ there is already a deficit in muscle strength, both concentric and eccentric, of the periarticular muscles of the hip and functional deficits. Regarding electrical activity, only the gluteus maximus in eccentric abduction changed.
Strength and electrical activity of hip muscles in individuals with hip osteoarthritis
Keywords: Osteoartrite; Capacidade funcional; Qualidade de vida; Força muscular; Eletromiografia; Fisioterapia; Osteoarthritis; Functionality; Quality of life; Muscular strength; Electromyography; Physiotherapy; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL